Molecular Mechanisms in the Genesis of Seizures and Epilepsy Associated With Viral Infection - Löscher, Wolfgang; Howe, Charles L. (Frontiers in Molecular Neuroscience, 2022)
Seizures are a common presenting symptom during CNS viral infections and can occur during the initial phase of infection (“early” or acute symptomatic seizures), after recovery (“late” or spontaneous seizures, indicating the development of acquired epilepsy), or both. The development of acute and delayed seizures may have shared as well as unique pathogenic mechanisms and prognostic implications. Based on an extensive review of the literature, we present an overview of viruses that are associated with early and late seizures in humans. We then describe potential pathophysiologic mechanisms underlying ictogenesis and epileptogenesis, including routes of neuroinvasion, viral control and clearance, systemic inflammation, alterations of the blood-brain barrier, neuroinflammation, and inflammation-induced molecular reorganization of synapses and neural circuits. We provide clinical and animal model findings to highlight commonalities and differences in these processes across various neurotropic or neuropathogenic viruses, including herpesviruses, SARS-CoV-2, flaviruses, and picornaviruses. In addition, we extensively review the literature regarding Theiler’s murine encephalomyelitis virus (TMEV). This picornavirus, although not pathogenic for humans, is possibly the best-characterized model for understanding the molecular mechanisms that drive seizures, epilepsy, and hippocampal damage during viral infection. Enhanced understanding of these mechanisms derived from the TMEV model may lead to novel therapeutic interventions that interfere with ictogenesis and epileptogenesis, even within non-infectious contexts.